2014
DOI: 10.1242/jcs.154542
|View full text |Cite
|
Sign up to set email alerts
|

CD44 regulates dendrite morphogenesis through Src tyrosine kinase-dependent positioning of the Golgi apparatus

Abstract: The acquisition of proper dendrite morphology is a crucial aspect of neuronal development towards the formation of a functional network. The role of the extracellular matrix and its cellular receptors in this process has remained enigmatic. We report that the CD44 adhesion molecule, the main hyaluronan receptor, is localized in dendrites and plays a crucial inhibitory role in dendritic tree arborization in vitro and in vivo. This novel function is exerted by the activation of Src tyrosine kinase, leading to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 75 publications
0
30
1
Order By: Relevance
“…E11 binds to CD44, a molecule also expressed in neuronal dendrites, 25 and expression of either molecule has been associated with osteocytic dendrite branching. 26, 27 Osteocytic dendrites also contain α-actinin and fimbrin, actin-bundling proteins required for the cytoskeletal organization of osteocytes isolated from chicken.…”
Section: Molecular and Functional Signature Of Osteocytesmentioning
confidence: 99%
“…E11 binds to CD44, a molecule also expressed in neuronal dendrites, 25 and expression of either molecule has been associated with osteocytic dendrite branching. 26, 27 Osteocytic dendrites also contain α-actinin and fimbrin, actin-bundling proteins required for the cytoskeletal organization of osteocytes isolated from chicken.…”
Section: Molecular and Functional Signature Of Osteocytesmentioning
confidence: 99%
“…However, growth of dorsal root ganglion neurons on a hyaluronan substrate reduces neurite extension49. Further, the major hyaluronan receptor CD44 is expressed on neuronal dendrites, and blockade of CD44 increases dendritic arborisation of cortical and hippocampal neurons both in vitro and in vivo 50. Conversely, blockade of RHAMM, another hyaluronan receptor, inhibits neurite extension in cultures of primary neurons and other neural cell lines51.…”
Section: Discussionmentioning
confidence: 99%
“…All three intracellular messengers that we evaluated, PKA, PKC and Src, have also been associated to CD44 receptor signaling (Lee et al, 2008; Bourguignon et al, 2009; Bourguignon et al, 2010; Campo et al, 2010; Zhang et al, 2014). Although it has not been established how CD44 interacts with PKA, it has been shown that CD44 can directly activate PKC (Bourguignon et al, 2009; Campo et al, 2010), and members of the Src family kinases are considered crucial for CD44 signaling (Ponta et al, 2003; Skupien et al, 2014; Dzwonek and Wilczynski, 2015). To directly activate the CD44 receptor we used the peptide A6 (Piotrowicz et al, 2011; Finlayson, 2015); its administration produced robust hyperalgesia that was inhibited by both the CD44 antagonist A5G27 and HMWH, confirming the action of A6 on the CD44 receptor.…”
Section: Discussionmentioning
confidence: 99%